Improving Adherence to Evidence-Based Guidelines for Chemotherapy-Induced Nausea and Vomiting. (July 2015) - Wood, Margaret; Hall, Laura; Hockenberry, Marilyn; Borinstein, Scott
Chemotherapy-induced nausea and vomiting (CINV) is one of the most common side effects experienced by patients receiving chemotherapy. Antiemetic medications can be used to effectively prevent and treat CINV. Choice and dose of antiemetics are often based on provider preference rather than evidenced-based information. CINV antiemetic prescribing guidelines provide an evidence-based approach and standardization for the management of this common side effect. The purpose of this quality improvement project was to improve adherence to CINV antiemetic guidelines. Despite distribution of CINV guidelines, there was inconsistent compliance with their use. When providers reported unfamiliarity with the guidelines, they were reintroduced and direct provider feedback was given to improve adherence. This quality improvement project demonstrates the need for continued reinforcement to sustain change that results in the best care for children experiencing CINV.